A novel role for ceramide synthase 6 in mouse and human alcoholic steatosis. Issue 1 (1st September 2017) - Williams, Bianca; Correnti, Jason; Oranu, Amanke; Lin, Annie; Scott, Victoria; Annoh, Maxine; Beck, James; Furth, Emma; Mitchell, Victoria; Senkal, Can E.; Obeid, Lina; Carr, Rotonya M.
Abstract : Perilipin 2 (PLIN2) is a lipid‐droplet protein that is up‐regulated in alcoholic steatosis and associated with hepatic accumulation of ceramides, bioactive lipids implicated in alcoholic liver disease pathogenesis. The specific role of ceramide synthetic enzymes in the regulation of PLIN2 and promotion of hepatocellular lipid accumulation is not well understood. We examined the effects of pharmacologic ceramide synthesis inhibition on hepatic PLIN2 expression, steatosis, and glucose and lipid homeostasis in mice with alcoholic steatosis and in ethanol‐incubated human hepatoma VL17A cells. In cells, pharmacologic inhibition of ceramide synthase reduced lipid accumulation by reducing PLIN2 RNA stability. The subtype ceramide synthase (CerS)6 was specifically up‐regulated in experimental alcoholic steatosis in vivo and in vitro and was up‐regulated in zone 3 hepatocytes in human alcoholic steatosis. in vivo ceramide reduction by inhibition of de novo ceramide synthesis reduced PLIN2 and hepatic steatosis in alcohol‐fed mice, but only de novo synthesis inhibition, not sphingomyelin hydrolysis, improved glucose tolerance and dyslipidemia. These findings implicate CerS6 as a novel regulator of PLIN2 and suggest that ceramide synthetic enzymes may promote the earliest stage of alcoholic liver disease, alcoholic steatosis.—Williams, B., Correnti, J., Oranu, A., Lin, A., Scott, V., Annoh, M., Beck, J., Furth, E., Mitchell, V., Senkal, C. E., Obeid, L., Carr, R. M. A novel role for ceramide synthase 6 in mouse and human alcoholic steatosis. FASEB J. 32, 130‐142 (2018). www.fasebj.org